Exploring Indonesian Traditional Sticky Rice Based Snacks: A Systematic Review - Nur Agustin Mardiana (Universitas Islam Raden Rahmat, Malang, 2025)
In Indonesia, glutinous rice is a fundamental ingredient in a wide array of traditional snacks. Despite its cultural importance, there is a notable lack of comprehensive academic reviews specifically addressing traditional Indonesian snacks made from glutinous rice flour. To address this gap, the present study aims to identify and categorize various traditional snacks derived from glutinous rice, while also examining their cultural significance within local communities. A systematic approach was employed, utilizing keyword searches and Boolean phrase logic to gather relevant data. Sources included books, peer-reviewed journals, reputable websites, and other forms of online literature. The study identified 44 food out of 200 papers made from glutinous rice. Beyond their function as consumables, these culinary products are deeply woven into the fabric of Indonesian culture, often playing central roles in religious ceremonies, traditional rituals, and other cultural practices.